Crystallization and preliminary X‐ray diffraction analysis of the Csu pili CsuC–CsuA/B chaperone–major subunit pre‐assembly complex from Acinetobacter baumannii. Issue 6 (1st June 2015) - Pakharukova, Natalia; Tuittila, Minna; Paavilainen, Sari; Zavialov, Anton
<x xml:space="preserve">Abstract</x> The attachment of many Gram‐negative pathogens to biotic and abiotic surfaces is mediated by fimbrial adhesins, which are assembled via the classical, alternative and archaic chaperone–usher (CU) pathways. The archaic CU fimbrial adhesins have the widest phylogenetic distribution, yet very little is known about their structure and mechanism of assembly. To elucidate the biogenesis of archaic CU systems, structural analysis of the Csu fimbriae, which are used by Acinetobacter baumannii to form stable biofilms and cause nosocomial infection, was focused on. The major fimbriae subunit CsuA/B complexed with the CsuC chaperone was purified from the periplasm of Escherichia coli cells co‐expressing CsuA/B and CsuC, and the complex was crystallized in PEG 3350 solution using the hanging‐drop vapour‐diffusion method. Selenomethionine‐labelled CsuC–CsuA/B complex was purified and crystallized under the same conditions. The crystals diffracted to 2.40 Å resolution and belonged to the hexagonal space group P6422, with unit‐cell parameters a = b = 94.71, c = 187.05 Å, α = β = 90, γ = 120°. Initial phases were derived from a single anomalous diffraction (SAD) experiment using the selenomethionine derivative.